Strategy Analysis of PT. Sumber Alfaria Trijaya TBK - Khoirunissa, Alvi Diani; Ramdani, Luki; Kaltum, Umi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to analyze the strategy of PT Sumber Alfaria Trijaya, Tbk. by using a SWOT analysis consisting of a matrix of IFAS (Internal Factor Analysis Strategy), EFAS (External Factor Analysis Strategy) as a basis for identifying the strengths and weaknesses of the company. This study uses descriptive qualitative research methods to explain external factors and internal factors in the company. The results of the study show that PT Sumber Alfaria Trijaya Tbk is a leader in the retail business in Indonesia which still needs support in the form of large promotions and expansions and is in a strong position and has great growth potential in the future. This research contributes to expanding understanding of the business strategy of PT Sumber Alfaria Trijaya Tbk and provides advice for making the right decisions in developing the business in the future.